The Importance of Basic Sanitation Management for Water Resources - Castro, Bruno Vilas Boas de; Broch, Synara Aparecida Olendzki (Technical and Scientific Journal Green Cities, 2025)
Objective: To discuss, through a literature review, the importance of basic sanitation management for the preservation and sustainable use of water resources, analyzing how the absence or deficiency of sanitation infrastructure compromises water quality, public health, and environmental balance.Methodology: The research used a qualitative approach, based on a literature review and bibliometric analysis. The Web of Science and Scopus databases were consulted, covering the period 2005 to 2024, with the aim of identifying trends, gaps, and the evolution of scientific literature on basic sanitation and water resources.Originality and Relevance: The study stands out for integrating the dimensions of basic sanitation and water security from an interdisciplinary perspective, linking aspects of regulation, environmental planning, and public policies. The research reinforces the importance of sanitation as a strategic instrument for water governance and sustainability. Results: The findings indicate that the lack of basic sanitation is one of the main causes of water pollution and water insecurity in Brazil. It was found that the country has a high level of scientific production on the topic, but still faces challenges in effectively implementing public policies for universal access and integrated management of services.Theoretical and Methodological Contributions: The work expands the theoretical framework by treating sanitation as an essential component of water resource management and water security. Methodologically, the research consolidates the combined use of literature review and bibliometric analysis as effective tools for understanding trends and guiding future research on environmental governance and sustainability.Social and Environmental Contributions: The results reinforce that basic sanitation is crucial for improving living conditions, promoting public health, and reducing social inequalities. Environmentally, it contributes to the protection of water sources, the restoration of ecosystems, and the strengthening of water security, constituting an essential pillar of sustainable development
Keywords: Water Resources; Basic Sanitation; Water Security